Geochemical investigation of tar balls collected on a beach on Žirje island (Croatia) using petroleum biomarkers - Marinović, Slavica, inženjerka kemije; Fajković, Hana; Cuculić, Vlado (2021)
Tar balls are frequently reported as indicators of the extent of marine pollution owing to spill incidents of crude oil or petroleum products. Representative tar ball samples collected on a beach on Žirje Island, Croatia, were geochemically characterised by gas chromatography coupled to mass spectrometry (GC/MS) in order to identify correlations between them and investigate potential sources. The chemical analysis of petroleum biomarkers, hopanes, and steranes, detected by gas chromatography/mass spectrometry (GC/MS) generates information of great importance to environmental forensic investigations in terms of determining the source of spilled oil, differentiating and correlating oils, and monitoring the degradation process and weathering state of oils under a wide variety of conditions. The chromatographic signatures of hopane and sterane biomarkers in tar ball samples from Žirje Island were compared. Characteristic hopane and sterane fingerprints show that all the tar ball samples originated from crude oil spills. This study indicates that, the major source of tar balls was likely to be the same type of crude oil as evident from the petroleum biomarker fingerprints.
Katranske kuglice često se navode kao pokazatelji stupnja zagađenja mora uslijed incidenata izlijevanja nafte ili naftnih proizvoda. Reprezentativni uzorci katranskih kuglica prikupljeni na hrvatskoj plaži otoka Žirja geokemijski su karakterizirani vezanim sustavom plinska kromatografija/masena spektrometrija (GC/MS) kako bi se utvrdila njihova povezanost i istražili potencijalni uzroci zagađenja. Kemijskom analizom naftnih biomarkera, hopana i sterana dobivenih plinskom kromatografijom sa spektrometrijom masa dolazi se do informacija velike važnosti za forenzička ispitivanja okoliša u smislu utvrđivanja izvora onečišćenja (nafta ili naftni proizvodi), njihovog razlikovanja i korelacije, kao i praćenja procesa njihove razgradnje i isparavanja u različitim vremenskim uvjetima. Uspoređeni su kromatogrami biomarkera, hopana i sterana, uzoraka katranskih kuglica s otoka Žirja. Karakteristični hopanski i steranski fragmentogrami pokazuju da sve katranske kuglice potječu od incidenata izlijevanja nafte. Ovo istraživanje pokazuje da je glavni uzrok pojave katranskih kuglica vjerojatno isti tip sirove nafte, što je vidljivo iz naftnih biomarkera.
Bibliografija: 16 jed.
Abstract ; Sažetak.
Keywords: Katranske kuglice -- Izlijevanje nafte -- Naftni biomarkeri -- GC/MS metoda